CHARACTERS' IMPOLITENESS IN PARANORMAN MOVIE - Abimanto, Dhanan; Oktavia, Ariana; Aprillina, Aprillina; Suci Aris Yuliatin, Anna (Universitas Maritim AMNI Semarang, 2023)
This research used a qualitative method. The data were utterances uttered by characters in the Paranorman movie, whereas the contexts were dialogues. The research used the Paranorman movie script and movie as sources. The researcher was the primary instrument, with the data sheet as a secondary. The researcher collected data through analyzing documents by note-taking. The data were analyzed using a reference. The results of the research are as follows. First, other characters in Paranorman use four types of impoliteness strategies. They are bald on record impoliteness, positive impoliteness, negative impoliteness, and sarcasm. Second, each impoliteness strategy has its own representation. Direct, clear, and unambiguous statements are used to express impoliteness. Positive impoliteness occurs as disassociating from others, calling the other names, and using of taboo words. Negative impoliteness occurs as condescending, scorning, or ridiculing the other. Sarcasm or mock politeness is only performed by using insincere politeness. This is the most representation. Third, the movie shows three responses: no response, accepting, and countering the face attack. Countering a face attack has two parts: offensive and defensive.